Comparison of Dietary Modifications with and without Aerobic Exercises in Improving the Cholesterol Lipid Profile for Treatment of Hyperlipidemia-Naïve Patients: Comparison of Dietary Modifications - Nazar, Qurrat-ul-ain; Hamid, Faizan; Javed, Ahsan; Ilyas, Zubair bin; Nawazish, Sameera; Aleem, Muhammad Irfan; Mubashir, Usman; Muhammad Arsalan, Hafiz Rana (Pakistan Journal of Health Sciences, 2023)
Hyperlipidemia describes a condition in which an abnormal mass metabolism brought on by a variety of factors raises blood cholesterol levels. According to epidemiological research, there is a strong link between the lipoprotein profile and cardiovascular morbidity and mortality, and those who are physically active have a 30 to 50% lower chance of developing cardiovascular disease. Objective: To compare the effect of dietary modifications with and without aerobic exercises in improving the cholesterol lipid profile for treatment of Hyperlipidemia-Naïve patients. Methods: The random sampling technique with random allocation done through the Lottery method. Lipid Profile Test was used as measuring tool. Whole procedure went through three steps: Pre-Labs Testing, 10 - Weeks Intervention Sessions, and Post-Labs Testing. 24 patients were randomly divided into two groups i.e., Experimental Group and the Control Group, each with 12 patients. After the intervention plan, results were analyzed, organized and interpreted. Results: Normally distributed variables were HDL-C, Cholesterol and VLDL-C with p > 0.05. Whereas, Triglycerides and LDL-C were not distributed normally i.e., p < 0.05. After the exercise program accomplished as instructed, a statistically significant decrease was observed in the values of Cholesterol, HDL-C, and VLDL-C with the value of p <0.05 for experimental group. However, values of Triglycerides and LDL-C were significantly decreased for the control group. Conclusions: The inclusion of aerobic exercises along with dietary changes substantially enhanced the patient's lipid profile, and exercise program's scope was adequate to produce meaningful changes in the body lipid composition of the study volunteers.